Strength of Block Masonry Walls Subject to Lateral Loading - Essawy, Sherif Aly Ahmed (My University, 1986)
Provisions for the design of masonry walls is subject to uniformly distributed pressure normal to the surface of the wall differ significantly from country to country. These differences may be attributed both to differences in design philosophy and to a general lack of conclusive or widely accepted experimental and analytical research. Most of the previous research in this area was concerned with brick masonry and with practical rather than well defined support conditions. Also, the available design methods were not accurate or rational. Therefore, this study was initiated to investigate the flexural behaviour of hollow concrete block masonry both experimentally and analytically and to assess the design methods for laterally loaded walls.
The experimental program included 30 full scale wall tests representing different support conditions and aspect ratios. In addition, stack bonded prisms and wallettes were used to determine the flexural tensile strengths. The full scale tests were performed using a test facility designed to accommodate tests of masonry panels up to 6.0 m long by 3.6 m high and to provide well defined support conditions. The observed behaviours of the walls were compared to other walls of the same series and to other tests to investigate the effects of variability, aspect ratio, support conditions, and the presence of either precompression along the top panel or precracking near the panel center.
A nonlinear finite element model capable of reproducing the observed behaviour of the walls was developed and used to extend the knowledge of masonry wall behaviour to include untested conditions and configurations. In this model, the anisotropic nature of the masonry, the nonlinearity due to cracking, and the effects of the transverse shear were taken into considerations. Also, the existing biaxial failure criteria were examined and proposed macroscopic biaxial failure criterion was incorporated in the finite element model to predict the strengths and the failure modes for masonry assemblages. This criterion accounted for the anisotropic and composite nature of masonry and was based on physical interpretations rather than being strictly a phenomenological criterion.
Finally, the available design methods were compared using the extended data from the analytical model and design a method based on elastic plate theory was proposed. This method was rationally developed to predict first cracking and failure capacities for masonry panels simply supported on three or four sides for a wide range of aspect ratios.
Keywords: Civil and Environmental Engineering; Other Civil and Environmental Engineering; Civil and Environmental Engineering